Modeling of Airborne Bathymetric Lidar Waveforms - Kim, Minsu; Kopilevich, Yuri; Feygels, Viktor; Park, Joong Yong; Wozencraft, Jennifer (Journal of coastal research, 2016)
Kim, M.; Kopilevich, Y.; Feygels, V.; Park, J.Y., and Wozencraft, J., 2016. Modeling of airborne bathymetric lidar waveforms. In: Brock, J.C.; Gesch, D.B.; Parrish, C.E.; Rogers, J.N., and Wright, C.W. (eds.), Advances in Topobathymetric Mapping, Models, and Applications. Journal of Coastal Research, Special Issue, No. 76, pp. 18–30. Coconut Creek (Florida), ISSN 0749-0208. Modeling the optical power of the lidar return waveform is performed for the radiometrically calibrated CZMIL (Coastal Zone Mapping and Imaging Lidar, Optech, Inc.) data. For this purpose, a lidar waveform simulator was developed. The theory is described based on the receiver sensitivity function, the radiative transfer equation (RTE) via the Greens function, the optical reciprocity theorem, and the small angle approximation (SAA). The SAA-based RTE is solved for the radiance distribution using the Fourier transform method. Along with the numerical algorithms, the contribution was made on the air-water and water-bottom interface peaks in the bathymetric lidar waveforms. Lacking ground truth data, a simulated waveform that best fits CZMIL data was used to estimate the optimized environmental parameters. The estimated parameters were well within the plausible natural optical properties. Compared to other approaches based on the relative intensity waveform, the simulation was applied to the absolute calibrated power. Thus, the model can be used to predict the general performance of any bathymetric lidar. This research will help design an optimized system to achieve the maximum performance. The forward modeling capability will also provide opportunities to develop advanced waveform processing algorithms, such as surface peak modeling and scattering correction. Thus, the improved quality of bathymetric lidar data contributed by this research will promote the various coastal science applications in terms of improved data accuracy and extended coverage.